Aerodynamic Characteristics of Individual Ballast Particle by Wind Tunnel Tests - G.Q. Jing; G.X. Liu; J. Lin; J. Martinez; C.T. Yin (Journal of Engineering Science and Technology Review, 2014)
Ballast flying has been considered as a problem in train aerodynamics with increasing the maximal speed. And this phenomenon seriously threats the safety of train operation. However, aerodynamic characteristics of individual ballast were less studied in the previous literature. This paper describes an investigation of the aerodynamic effect of ballast particles by wind tunnel tests. It considers the nature of the wind and ballast physical characteristics. A simple method for calculating the wind effects by CFD is set out, ballast particles were classified according to their shapes and mass in order to investigate the influence of the wind velocity, wind pressure and other parameters on displacement of ballast particles. Two sets of wind tunnel tests were performed under the conditions that ballast particles were movable and unmovable on the platform respectively. The tests data and reasonable explanations were given, as well as the CFD simulations of individual ballast particles.